2002
DOI: 10.1055/s-2002-25277
|View full text |Cite
|
Sign up to set email alerts
|

Do Explicit Appropriateness Criteria Enhance the Diagnostic Yield of Colonoscopy?

Abstract: The use of detailed and explicit appropriateness criteria for colonoscopy significantly enhances the identification of relevant lesions and in particular of colon cancer. The use of such criteria could therefore improve patient selection for colonoscopy and thus contribute to efforts aimed at enhancing the quality and efficiency of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 19 publications
4
47
3
1
Order By: Relevance
“…In the study of Chan et al, only indication of rectal bleeding in multivariate analysis was predictive for colonic lesions. The fact that gastroenterologist [20,23], male sex [15,31], exploration of iron deficiency anemia [14] or rectal bleeding [24] and older age of patients [16,31] were factors associated with colonic lesion was also found in several studies. Colonic functional disorders was, in absence of signs of severity (weight loss, anemia, rectal bleeding, nocturnal recurdescence of signs and family history of colorectal cancer) associated to a low diagnosis yield of colonoscopy according to Schüssele et al [30].…”
Section: Open Accessmentioning
confidence: 89%
See 2 more Smart Citations
“…In the study of Chan et al, only indication of rectal bleeding in multivariate analysis was predictive for colonic lesions. The fact that gastroenterologist [20,23], male sex [15,31], exploration of iron deficiency anemia [14] or rectal bleeding [24] and older age of patients [16,31] were factors associated with colonic lesion was also found in several studies. Colonic functional disorders was, in absence of signs of severity (weight loss, anemia, rectal bleeding, nocturnal recurdescence of signs and family history of colorectal cancer) associated to a low diagnosis yield of colonoscopy according to Schüssele et al [30].…”
Section: Open Accessmentioning
confidence: 89%
“…Carrion et al based on the EPAGE II criteria had also reported 94% of applicability [14]. Bosset et al with a Swiss criteria noted applicability of 96% [15]. However, Fernández-Esparrach et al had observed a rather smaller proportion (80%) applicable indication with the EPAGE II criteria [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duration of protection against disease and carriage are important in estimating how many cases can be prevented and thus the potential cost-effectiveness of the vaccine. The impact of such vaccines in high income countries may have resulted more from the excellent direct and herd protection amongst adolescents and young adults than from the short duration responses induced by the vaccination of young children [8]. The reasons for these age-dependent differences in immunity are not completely understood but may relate to developmental differences in the immune system, or be driven by environmental factors.…”
mentioning
confidence: 99%
“…Generally, bactericidal titers of ≥1:4 in human serum are considered protective against IMD [7]. Titers as high as 1:128 in rabbit serum are needed to assure that a titer of 1:4 are present, if measured with human serum [8]. Despite this shortcoming, the results of this bridging study are adequately reassuring regarding efficacy and safety of this vaccine in the Indian context.…”
mentioning
confidence: 99%